Health Seeking Behaviour pada Perawatan Kanker - Rufli, Arza; Afiyanti, Yati; Hargiana, Giur (Journal of Telenursing (JOTING), 2024)
This study aims to synthesize the findings from existing research on health-seeking behaviors among cancer patients. A systematic review was conducted using electronic databases and websites, including Sage Journal, ProQuest, and Science Direct, on March 9, 2024. The search strategy employed a combination of MeSH terms and keywords, specifically "health-seeking behavior," "cancer care," and "cancer prevention." The analysis revealed that, out of 11 research articles reviewed, several reported a low incidence of health-seeking behavior, particularly in communities within developing countries. This was largely attributed to limited access to healthcare facilities, leading some patients to rely solely on traditional medicine. In conclusion, the decision to seek medical assistance in some communities is complex and influenced by various factors. Keywords: Cancer Care, Cancer Prevention. Health Seeking Behavior.